Clinical and Laboratory Features of Enteroviral Meningitis in Children in Modern Conditions (According to the Data of Yaroslavl Region) - S. N. Eshmolov; I. G. Sitnikov; I. M. Melnikova (Детские инфекции (Москва))
152 cases of enteroviral meningitis in children aged 3 to 17 years were analyzed. All the patients were treated in the Municipal Health Care Institution «Clinical Hospital for Infectious Diseases No1» in Yaroslavl. The predominance of moderate forms of the disease with hypertensive syndrome was determined. An imbalance of the cytokine profile in the acute phase of the disease was registered. This was due to the increased production of pro-inflammatory cytokines and a decrease of protective role of anti-inflammatory cytokines. Despite relatively favorable course, there remained a high risk of formation of functional and organic disorders on the part of the nervous system in the period of convalescence, which creates ground for review and amendment of the standard protocols of treatment programs and including preparations of etiotropic direction. The authors tested therapeutic schemes and defined clinical and immunological efficacy of antiviral drugs Amixin and Arbidol with antiviral and interferonogenic effects as a part of complex basic therapy for enteroviral meningitis in children. In addition, the authors analyzed the results of follow-monitoring of 87 convalescents 3 months after their discharge from hospital. The results confirm the necessity and appropriateness of inclusion of preparations of etiotropic direction, in particular the antiviral preparations Arbidol and Amixin in standards of basic therapy of enteroviral meningitis in children.